Implementing Lifecycle-Based Clustering and Digital Integration in Indonesia’s Primary Healthcare: A Policy Analysis of Family Medicine’s Role in Sustainable Care - Handoko, Marshell Timotius (Jurnal Ar Ro'is Mandalika (Armada), 2025)
Transforming primary healthcare in Indonesia through integrated, lifecycle-based approaches is a strategic effort to achieve a high-value, high-quality health system. This study analyzes the role of family medicine within Indonesia’s primary care model, highlighting how family doctors contribute to improved healthcare accessibility, continuity, and responsiveness. Family doctors serve as frontline providers across lifecycle clusters—including maternal and child health, productive adult care, elderly care, and infectious disease control. Their role in managing chronic illnesses, mental health, and preventive care is essential within the Indonesian context, as they deliver comprehensive services that address the biological, psychological, and social determinants of health. Digital integration through the Platform Satu Sehat and the Pemantauan Wilayah Setempat (PWS) dashboard supports real-time health monitoring, enabling family doctors to make data-driven decisions and provide proactive care. In addition, family doctors extend their impact through community engagement, leading immunization campaigns, health education, and public health initiatives. They also serve as patient advocates by coordinating multidisciplinary teams and guiding individuals through complex healthcare pathways. This Indonesia-based model demonstrates the potential of family medicine to drive sustainable, community-based primary care transformation and provides a replicable framework for other low- and middle-income countries. The findings reinforce the critical role of family doctors as a foundation for equitable access, improved quality of care, and resilient health systems.